Life style factors associated with overweight and obesity in Nepalese women of reproductive age - Upadhyay-Dhungel, Kshitiz; Paudel, Pramod; Prakash, Satyam; Yadav, Sudeep Kumar (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Overweight and Obesity is a highly prevalent global epidemic. South Asians are more vulnerable to obesity-related diseases with rising co-morbidities when compared to developed countries. It is linked with several health complications. Globally more women are found overweight or obese compared to men. So this study is planned to examine the life-style related determinants of overweight and obesity in reproductive aged females (15-49 years) in Nepal. Material and Methods: Analytical cross-sectional study was carried out among reproductive aged females (15-49 years) of Kathmandu Metropolitan city, Nepal. Stratified random as well as population proportionate sampling technique was used to determine number of respondents from each selected ward. A structured questionnaire for nutrition intake and various demographic and lifestyle factors reviewed by the panel of experts was administered for data collection. Overweight or obesity was considered as per BMI international cut-off points for adults. Results: Overweight or obesity (BMI≥25) in reproductive aged females was found to be 26%. Women who were working, married, and had family history of overweight and obesity and those who took fast foods moderately were found significantly more likely of becoming overweight or obese (p < 0.05). Moderate physical activity, daily breakfast intake, were found to be significantly less likely of becoming overweight or obese in reproductive aged women (p < 0.05). Conclusions: Moderate physical activities as well as daily breakfast consumption is more likely to reduce overweight and obesity. The findings can be used as a guideline for overweight and obesity prevention in reproductive aged women. Some larger prospective studies are needed.